A kind of anti-ultraviolet TPU high and low temperature film and preparation method thereof
By adding a specific proportion to the TPU membrane, a complicated agent based on Ellow Stone, a silicane coupling agent, flame retardant, thermal stabilizer, lubricant, and antioxidant, the plasticization of the film blower machine Squeezing and bloating traction processes have prepared high -low temperature -resistant TPU -resistant TPUs, solving the problem of insufficient flame retardant performance and stability of the existing TPU membrane, and achieved efficient flame retardant and separation performance.
Patent Information
- Application Number
- CN202411434405.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-15
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TPU films, and in particular to an anti-ultraviolet TPU high and low temperature film and a preparation method thereof. Background Art
[0002] Thermoplastic polyurethane (TPU) is a linear block polymer composed of chain extenders, diisocyanates, and polyols. The modulus of TPU is between that of plastic and rubber, so it has both plasticity and elasticity, and has excellent mechanical properties, superior cold resistance, high wear resistance, oil resistance, and ozone resistance. It has been widely used in medical treatment, equipment, light industry, etc.
[0003] The existing TPU film has poor flame retardancy, and it is difficult to coordinate and balance the improvement of flame retardancy and barrier properties. At the same time, the product has poor UV resistance and high and low temperature stability, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an anti-ultraviolet TPU high and low temperature film and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides an anti-ultraviolet TPU high and low temperature film, comprising the following raw materials in parts by weight:
[0007] 75-85 parts of TPU resin, 8-12 parts of anti-adjustment agent, 6-9 parts of filler based on halloysite modification, 5-8 parts of silane coupling agent, 5-7 parts of flame retardant, 4-6 parts of heat stabilizer, 2-4 parts of lubricant, 2-5 parts of antioxidant.
[0008] Preferably, the heat stabilizer is calcium stearate, the flame retardant is magnesium hydroxide; the lubricant is microcrystalline wax; the antioxidant is antioxidant 1010; and the silane coupling agent is silane coupling agent KH560.
[0009] Preferably, the preparation method of the adjustment-resistant material is:
[0010] S11: Add 2 to 3 parts of silane coupling agent KH550 and 1 to 3 parts of sodium alginate powder to 5 to 8 parts of lanthanum chloride solution by weight and mix well to obtain modified lanthanum chloride solution;
[0011] S12: The flaky boron nitride is firstly mixed in a 4% potassium permanganate solution with a mass fraction of 3 to 5 times the total weight of the flaky boron nitride, and then washed with water and dried to obtain dry flaky boron nitride;
[0012] Then, the dried flake boron nitride, sodium dodecylbenzene sulfonate solution and modified lanthanum chloride solution are mixed thoroughly in a weight ratio of (3-5):(4-7):2 to obtain a flake boron nitride regulating solution;
[0013] S13: The flake boron nitride adjusting liquid and the resistance agent are mixed in a weight ratio of 7:5 and ball-milled at a ball-milling speed of 1000-1200 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain the resistance agent.
[0014] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-4%.
[0015] Preferably, the preparation method of the resistance agent is:
[0016] The nano bentonite is preheated at 55-60°C for 20 minutes to obtain preheated nano bentonite; then, 5-8 parts of the preheated nano bentonite and 1-3 parts of nano zinc oxide are added to 5-8 parts of 5% by weight yttrium nitrate solution, and then 2-4 parts of 4% by weight chitosan solution and 1-3 parts of sodium lignin sulfonate are added and mixed and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a tolerizing agent.
[0017] Preferably, the stirring speed of the blending and stirring process is 750 to 850 r / min, and the stirring time is 35 to 45 min.
[0018] Preferably, the preparation method of the filler based on halloysite modification is:
[0019] S101: soaking the halloysite in a sufficient amount of a sodium hydroxide solution having a mass fraction of 6%, and then washing, filtering and drying after the soaking is completed;
[0020] Then stir evenly in a sufficient amount of 5% sodium citrate solution, wash with water, filter and dry;
[0021] S102: mixing hydroxyapatite and 2-5% by mass sodium silicate solution in a weight ratio of 2:5 to obtain hydroxyapatite liquid;
[0022] According to weight, 2 to 4 parts of stearic acid and 1 to 3 parts of wollastonite are added to 8 to 12 parts of 2 to 5% dopamine hydrochloride solution, and then 3 to 5 parts of hydroxyapatite liquid are added and mixed sufficiently to obtain a filling modifier;
[0023] S103: The halloysite treated in S101 and the filling modifier obtained in S102 are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water and dried to obtain a filling agent modified by halloysite.
[0024] Preferably, the soaking temperature of the soaking treatment in S101 is 48-52° C., and the soaking time is 1 hour; the rotation speed of the mixing and ball milling treatment in S103 is 1000-1500 r / min, and the ball milling time is 35-45 minutes.
[0025] The present invention also provides a method for preparing an ultraviolet resistant TPU high and low temperature film, comprising the following steps:
[0026] The resistant filler, halloysite-modified filler, flame retardant and heat stabilizer are first stirred and mixed, and then sent into a film blowing machine together with TPU resin, silane coupling agent, lubricant and antioxidant for plasticization and extrusion to obtain a plasticized extrudate; the plasticized extrudate is blown and pulled, and then cooled, pulled and rolled to obtain a UV-resistant TPU high and low temperature film.
[0027] Preferably, the feeding temperature in the film blowing machine is 135-140°C, the temperature of the plasticizing section is 170-175°C, and the die head temperature is 150°C; the blowing ratio of the inflation traction is 2.7-2.9, and the traction ratio is 4-6.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The TPU high and low temperature film of the present invention adopts TPU resin as the base material, adds silane coupling agent, flame retardant, stabilizer, lubricant and antioxidant as functional additives, and the TPU high and low temperature film obtained by mutual coordination and matching of the filler and the anti-adjustment agent based on halloysite modification has excellent flame retardant and barrier properties, and the product has significant UV resistance and high and low temperature stability effects;
[0030] 2. The anti-adjustment agent uses flake boron nitride treated with potassium permanganate solution, and then blended and coordinated with sodium dodecylbenzene sulfonate solution and modified lanthanum chloride solution. The lanthanum chloride solution, silane coupling agent KH550 and sodium alginate powder in the modified lanthanum chloride solution are fully mixed. The synergistic effect between flake boron nitride and the anti-adjustment agent is enhanced through the coordination and synergy between the raw materials. The flake boron nitride is used as the matrix, and the raw materials are matched and assisted. The nano-bentonite in the anti-adjustment agent is preheated, and then nano-zinc oxide, yttrium nitrate solution, 4% chitosan solution and sodium lignin sulfonate are mixed and stirred. The nano-zinc oxide assists the blending of yttrium nitrate solution, chitosan and other raw materials to enhance the synergy with the nano-bentonite. The nano-bentonite has a lamellar structure. The flake boron nitride adjusting liquid is enhanced and improved through the blending of nano-zinc oxide, so that the anti-adjustment agent obtained coordinates and improves the flame retardancy and barrier properties of the product in the product system. At the same time, the product has significant effects on UV resistance and high and low temperature stability.
[0031] 3. The filler based on halloysite modification is made by treating halloysite with sodium hydroxide solution and then stirring it in sodium citrate solution to optimize the activity and dispersion of halloysite. At the same time, hydroxyapatite and 2-5% sodium silicate solution are blended and coordinated. At the same time, stearic acid, wollastonite, dopamine hydrochloride solution and hydroxyapatite liquid are coordinated and assisted together. Hydroxyapatite is blended with needle-shaped wollastonite and combined with the halloysite system to enhance the resistance to adjustment, thereby further improving the performance of the product. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The anti-ultraviolet TPU high and low temperature film of this embodiment includes the following raw materials in parts by weight:
[0034] 75-85 parts of TPU resin, 8-12 parts of anti-adjustment agent, 6-9 parts of filler based on halloysite modification, 5-8 parts of silane coupling agent, 5-7 parts of flame retardant, 4-6 parts of heat stabilizer, 2-4 parts of lubricant, 2-5 parts of antioxidant.
[0035] The heat stabilizer in this embodiment is calcium stearate, the flame retardant is magnesium hydroxide; the lubricant is microcrystalline wax; the antioxidant is antioxidant 1010; and the silane coupling agent is silane coupling agent KH560.
[0036] The preparation method of the resistant agent of this embodiment is:
[0037] S11: Add 2 to 3 parts of silane coupling agent KH550 and 1 to 3 parts of sodium alginate powder to 5 to 8 parts of lanthanum chloride solution by weight and mix well to obtain modified lanthanum chloride solution;
[0038] S12: The flaky boron nitride is firstly mixed in a 4% potassium permanganate solution with a mass fraction of 3 to 5 times the total weight of the flaky boron nitride, and then washed with water and dried to obtain dry flaky boron nitride;
[0039] Then, the dried flake boron nitride, sodium dodecylbenzene sulfonate solution and modified lanthanum chloride solution are mixed thoroughly in a weight ratio of (3-5):(4-7):2 to obtain a flake boron nitride regulating solution;
[0040] S13: The flake boron nitride adjusting liquid and the resistance agent are mixed in a weight ratio of 7:5 and ball-milled at a ball-milling speed of 1000-1200 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain the resistance agent.
[0041] The mass fraction of the lanthanum chloride solution in this embodiment is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-4%.
[0042] The preparation method of the resistance agent of this embodiment is:
[0043] The nano bentonite is preheated at 55-60°C for 20 minutes to obtain preheated nano bentonite; then, 5-8 parts of the preheated nano bentonite and 1-3 parts of nano zinc oxide are added to 5-8 parts of 5% by weight yttrium nitrate solution, and then 2-4 parts of 4% by weight chitosan solution and 1-3 parts of sodium lignin sulfonate are added and mixed and stirred. After the stirring is completed, the mixture is filtered and dried to obtain a tolerizing agent.
[0044] The stirring speed of the blending and stirring process in this embodiment is 750 to 850 r / min, and the stirring time is 35 to 45 min.
[0045] The preparation method of the filler based on halloysite modification in this embodiment is:
[0046] S101: soaking the halloysite in a sufficient amount of a sodium hydroxide solution having a mass fraction of 6%, and then washing, filtering and drying after the soaking is completed;
[0047] Then stir evenly in a sufficient amount of 5% sodium citrate solution, wash with water, filter and dry;
[0048] S102: mixing hydroxyapatite and sodium silicate solution with a mass fraction of 2 to 5% in a weight ratio of 2:5 to obtain hydroxyapatite liquid;
[0049] According to weight, 2 to 4 parts of stearic acid and 1 to 3 parts of wollastonite are added to 8 to 12 parts of 2 to 5% dopamine hydrochloride solution, and then 3 to 5 parts of hydroxyapatite liquid are added and mixed sufficiently to obtain a filling modifier;
[0050] S103: The halloysite treated in S101 and the filling modifier obtained in S102 are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water and dried to obtain a filling agent modified by halloysite.
[0051] In S101 of this embodiment, the soaking temperature of the soaking treatment is 48-52° C., and the soaking time is 1 hour. In S103, the rotation speed of the mixing and ball milling treatment is 1000-1500 r / min, and the ball milling time is 35-45 minutes.
[0052] A method for preparing an anti-ultraviolet TPU high and low temperature film of this embodiment comprises the following steps:
[0053] The resistant filler, halloysite-modified filler, flame retardant and heat stabilizer are first stirred and mixed, and then sent into a film blowing machine together with TPU resin, silane coupling agent, lubricant and antioxidant for plasticization and extrusion to obtain a plasticized extrudate; the plasticized extrudate is blown and pulled, and then cooled, pulled and rolled to obtain a UV-resistant TPU high and low temperature film.
[0054] In the film blowing machine of this embodiment, the feeding temperature is 135-140° C., the temperature of the plasticizing section is 170-175° C., and the die head temperature is 150° C.; the blowing ratio of the inflation traction is 2.7-2.9, and the traction ratio is 4-6.
[0055] Embodiment 1: A UV-resistant TPU high and low temperature film, comprising the following raw materials in parts by weight:
[0056] 75 parts of TPU resin, 8 parts of anti-adjustment agent, 6 parts of filler based on halloysite modification, 5 parts of silane coupling agent, 5 parts of flame retardant, 4 parts of heat stabilizer, 2 parts of lubricant, and 2 parts of antioxidant.
[0057] The heat stabilizer in this embodiment is calcium stearate, the flame retardant is magnesium hydroxide; the lubricant is microcrystalline wax; the antioxidant is antioxidant 1010; and the silane coupling agent is silane coupling agent KH560.
[0058] The preparation method of the resistant agent of this embodiment is:
[0059] S11: Add 2 parts of silane coupling agent KH550 and 1 part of sodium alginate powder to 5 parts of lanthanum chloride solution by weight and mix well to obtain modified lanthanum chloride solution;
[0060] S12: The flaky boron nitride is firstly mixed in a 4% potassium permanganate solution with a mass fraction of 3 times the total weight of the flaky boron nitride, and then washed with water and dried to obtain dry flaky boron nitride;
[0061] Then, the dried flake boron nitride, the sodium dodecylbenzene sulfonate solution and the modified lanthanum chloride solution are mixed thoroughly in a weight ratio of 3:4:2 to obtain a flake boron nitride regulating solution;
[0062] S13: The flake boron nitride adjusting liquid and the resistance agent are mixed in a weight ratio of 7:5, and the ball milling is performed at a ball milling speed of 1000 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain the resistance agent.
[0063] The mass fraction of the lanthanum chloride solution in this embodiment is 2%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 2%.
[0064] The preparation method of the resistance agent of this embodiment is:
[0065] The nano bentonite was preheated at 55°C for 20 minutes to obtain preheated nano bentonite; then, 5 parts of the preheated nano bentonite and 1 part of nano zinc oxide were added to 5 parts of 5% by weight yttrium nitrate solution, and then 2 parts of 4% by weight chitosan solution and 1 part of sodium lignin sulfonate were added and mixed and stirred. After the stirring was completed, the mixture was filtered and dried to obtain a tolerizing agent.
[0066] The stirring speed of the blending and stirring process in this embodiment is 750 r / min, and the stirring time is 35 min.
[0067] The preparation method of the filler based on halloysite modification in this embodiment is:
[0068] S101: soaking the halloysite in a sufficient amount of a sodium hydroxide solution having a mass fraction of 6%, and then washing, filtering and drying after the soaking is completed;
[0069] Then stir evenly in a sufficient amount of 5% sodium citrate solution, wash with water, filter and dry;
[0070] S102: mixing hydroxyapatite and 2% sodium silicate solution by weight in a weight ratio of 2:5 to obtain hydroxyapatite solution;
[0071] According to weight, 2 parts of stearic acid and 1 part of wollastonite are added to 8 parts of 2% dopamine hydrochloride solution, and then 3 parts of hydroxyapatite liquid are added and mixed thoroughly to obtain a filling modifier;
[0072] S103: The halloysite treated in S101 and the filling modifier obtained in S102 are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water and dried to obtain a filling agent modified by halloysite.
[0073] In S101 of this embodiment, the soaking temperature of the soaking treatment is 48° C. and the soaking time is 1 hour. In S103, the rotation speed of the mixing and ball milling treatment is 1000 r / min and the ball milling time is 35 minutes.
[0074] A method for preparing an anti-ultraviolet TPU high and low temperature film of this embodiment comprises the following steps:
[0075] The resistant filler, halloysite-modified filler, flame retardant and heat stabilizer are first stirred and mixed, and then sent into a film blowing machine together with TPU resin, silane coupling agent, lubricant and antioxidant for plasticization and extrusion to obtain a plasticized extrudate; the plasticized extrudate is blown and pulled, and then cooled, pulled and rolled to obtain a UV-resistant TPU high and low temperature film.
[0076] In the film blowing machine of this embodiment, the feeding temperature is 135° C., the temperature of the plasticizing section is 170° C., and the die head temperature is 150° C.; the blowing ratio of the inflation traction is 2.7, and the traction ratio is 4.
[0077] Embodiment 2: A UV-resistant TPU high and low temperature film, comprising the following raw materials in parts by weight:
[0078] 85 parts of TPU resin, 12 parts of anti-adjustment agent, 9 parts of filler based on halloysite modification, 8 parts of silane coupling agent, 7 parts of flame retardant, 6 parts of heat stabilizer, 4 parts of lubricant, and 5 parts of antioxidant.
[0079] The heat stabilizer in this embodiment is calcium stearate, the flame retardant is magnesium hydroxide; the lubricant is microcrystalline wax; the antioxidant is antioxidant 1010; and the silane coupling agent is silane coupling agent KH560.
[0080] The preparation method of the resistant agent of this embodiment is:
[0081] S11: Add 3 parts of silane coupling agent KH550 and 3 parts of sodium alginate powder to 8 parts of lanthanum chloride solution by weight and mix well to obtain modified lanthanum chloride solution;
[0082] S12: The flaky boron nitride is firstly mixed in a potassium permanganate solution having a mass fraction of 4% which is 5 times the total weight of the flaky boron nitride, and then washed with water and dried to obtain dry flaky boron nitride;
[0083] Then, the dried flake boron nitride, the sodium dodecylbenzene sulfonate solution and the modified lanthanum chloride solution are mixed thoroughly in a weight ratio of 5:7:2 to obtain a flake boron nitride regulating solution;
[0084] S13: The flake boron nitride adjusting liquid and the resistance agent are mixed in a weight ratio of 7:5, and the ball milling is performed at a ball milling speed of 1200 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain the resistance agent.
[0085] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4%.
[0086] The preparation method of the resistance agent of this embodiment is:
[0087] The nano bentonite was preheated at 60°C for 20 minutes to obtain preheated nano bentonite; then, 8 parts of the preheated nano bentonite and 3 parts of nano zinc oxide were added to 8 parts of 5% by weight yttrium nitrate solution, and then 4 parts of 4% by weight chitosan solution and 3 parts of sodium lignin sulfonate were added and mixed and stirred. After the stirring was completed, the mixture was filtered and dried to obtain a tolerizing agent.
[0088] The stirring speed of the blending and stirring process in this embodiment is 850r / min, and the stirring time is 45min.
[0089] The preparation method of the filler based on halloysite modification in this embodiment is:
[0090] S101: soaking the halloysite in a sufficient amount of a sodium hydroxide solution having a mass fraction of 6%, and then washing, filtering and drying after the soaking is completed;
[0091] Then stir evenly in a sufficient amount of 5% sodium citrate solution, wash with water, filter and dry;
[0092] S102: mixing hydroxyapatite and 5% by mass sodium silicate solution in a weight ratio of 2:5 to obtain hydroxyapatite liquid;
[0093] By weight, 4 parts of stearic acid and 3 parts of wollastonite are added to 12 parts of 5% dopamine hydrochloride solution, and then 5 parts of hydroxyapatite liquid are added and mixed thoroughly to obtain a filling modifier;
[0094] S103: The halloysite treated in S101 and the filling modifier obtained in S102 are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water and dried to obtain a filling agent modified by halloysite.
[0095] In S101 of this embodiment, the soaking temperature of the soaking treatment is 52° C. and the soaking time is 1 hour. In S103, the rotation speed of the mixing and ball milling treatment is 1500 r / min and the ball milling time is 45 minutes.
[0096] A method for preparing an anti-ultraviolet TPU high and low temperature film of this embodiment comprises the following steps:
[0097] The resistant filler, halloysite-modified filler, flame retardant and heat stabilizer are first stirred and mixed, and then sent into a film blowing machine together with TPU resin, silane coupling agent, lubricant and antioxidant for plasticization and extrusion to obtain a plasticized extrudate; the plasticized extrudate is blown and pulled, and then cooled, pulled and rolled to obtain a UV-resistant TPU high and low temperature film.
[0098] In the film blowing machine of this embodiment, the feeding temperature is 140° C., the temperature of the plasticizing section is 175° C., and the die head temperature is 150° C.; the blowing ratio of the inflation traction is 2.9, and the traction ratio is 6.
[0099] Embodiment 3: A UV-resistant TPU high and low temperature film, comprising the following raw materials in parts by weight:
[0100] 80 parts of TPU resin, 10 parts of anti-adjustment agent, 7.5 parts of filler based on halloysite modification, 6.5 parts of silane coupling agent, 6 parts of flame retardant, 5 parts of heat stabilizer, 3 parts of lubricant, and 3.5 parts of antioxidant.
[0101] The heat stabilizer in this embodiment is calcium stearate, the flame retardant is magnesium hydroxide; the lubricant is microcrystalline wax; the antioxidant is antioxidant 1010; and the silane coupling agent is silane coupling agent KH560.
[0102] The preparation method of the resistant agent of this embodiment is:
[0103] S11: Add 2.5 parts of silane coupling agent KH550 and 2 parts of sodium alginate powder to 6.5 parts of lanthanum chloride solution by weight and mix well to obtain modified lanthanum chloride solution;
[0104] S12: The flaky boron nitride is firstly mixed in a 4% potassium permanganate solution having a mass fraction of 4 times the total weight of the flaky boron nitride, and then washed with water and dried to obtain dry flaky boron nitride;
[0105] Then, the dried flake boron nitride, the sodium dodecylbenzene sulfonate solution and the modified lanthanum chloride solution are mixed thoroughly in a weight ratio of 4:5.5:2 to obtain a flake boron nitride regulating solution;
[0106] S13: The flake boron nitride adjusting liquid and the resistance agent are mixed in a weight ratio of 7:5, and the ball milling is performed at a ball milling speed of 1100 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain the resistance agent.
[0107] The mass fraction of the lanthanum chloride solution in this embodiment is 3.5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 3%.
[0108] The preparation method of the resistance agent of this embodiment is:
[0109] The nano bentonite was preheated at 57.5°C for 20 minutes to obtain preheated nano bentonite; then, 6.5 parts of the preheated nano bentonite and 2 parts of nano zinc oxide were added to 6.5 parts of 5% by weight yttrium nitrate solution, and then 3 parts of 4% by weight chitosan solution and 2 parts of sodium lignin sulfonate were added and mixed and stirred. After the stirring was completed, the mixture was filtered and dried to obtain a tolerizing agent.
[0110] The stirring speed of the blending and stirring process in this embodiment is 800 r / min, and the stirring time is 40 min.
[0111] The preparation method of the filler based on halloysite modification in this embodiment is:
[0112] S101: soaking the halloysite in a sufficient amount of a sodium hydroxide solution having a mass fraction of 6%, and then washing, filtering and drying after the soaking is completed;
[0113] Then stir evenly in a sufficient amount of 5% sodium citrate solution, wash with water, filter and dry;
[0114] S102: mixing hydroxyapatite and 3.5% sodium silicate solution by weight in a weight ratio of 2:5 to obtain hydroxyapatite solution;
[0115] According to weight, 3 parts of stearic acid and 2 parts of wollastonite are added to 10 parts of 3.5% dopamine hydrochloride solution, and then 4 parts of hydroxyapatite liquid are added and mixed thoroughly to obtain a filling modifier;
[0116] S103: The halloysite treated in S101 and the filling modifier obtained in S102 are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water and dried to obtain a filling agent modified by halloysite.
[0117] In S101 of this embodiment, the soaking temperature of the soaking treatment is 50° C. and the soaking time is 1 hour. In S103, the rotation speed of the mixing and ball milling treatment is 1250 r / min and the ball milling time is 40 minutes.
[0118] A method for preparing an anti-ultraviolet TPU high and low temperature film of this embodiment comprises the following steps:
[0119] The resistant filler, halloysite-modified filler, flame retardant and heat stabilizer are first stirred and mixed, and then sent into a film blowing machine together with TPU resin, silane coupling agent, lubricant and antioxidant for plasticization and extrusion to obtain a plasticized extrudate; the plasticized extrudate is blown and pulled, and then cooled, pulled and rolled to obtain a UV-resistant TPU high and low temperature film.
[0120] In the film blowing machine of this embodiment, the feeding temperature is 137° C., the temperature of the plasticizing section is 172° C., and the die head temperature is 150° C.; the blowing ratio of the inflation traction is 2.8, and the traction ratio is 5.
[0121] Comparative Example 1:
[0122] The difference from Example 3 is that no anti-adjustment agent is added.
[0123] Comparative Example 2:
[0124] The difference from Example 3 is that no flake boron nitride conditioning liquid is added to the conditioning agent.
[0125] Comparative Example 3:
[0126] The difference from Example 3 is that no modified lanthanum chloride solution is added in the preparation of the flake boron nitride regulating solution.
[0127] Comparative Example 4:
[0128] The difference from Example 3 is that the modified lanthanum chloride solution is replaced by a 3.5% by mass lanthanum chloride solution.
[0129] Comparative Example 5:
[0130] The difference from Example 3 is that no resistance agent is added to the resistance agent.
[0131] Comparative Example 6:
[0132] The difference from Example 3 is that no filler based on modified halloysite is added.
[0133] Comparative Example 7:
[0134] The difference from Example 3 is that the filler based on halloysite modification is not treated with S101.
[0135] Comparative Example 8:
[0136] The difference from Example 3 is that the filler based on halloysite modification is not treated with a filler modifier.
[0137] Comparative Example 9:
[0138] The difference from Example 3 is that no hydroxyapatite liquid is added to the filling modifier.
[0139] Comparative Example 10:
[0140] The difference from Example 3 is that stearic acid and wollastonite are not added to the filling modifier.
[0141] Comparative Example 11:
[0142] The difference from Example 3 is that the dopamine hydrochloride solution is replaced by deionized water.
[0143] The flame retardant and barrier properties of the products of Examples 1-3 and Comparative Examples 1-11 were tested. The products were placed at -5°C for 24 hours, and then at 65°C for 24 hours. The test was repeated 5 times to test the high and low temperature stability of the products. The ultraviolet radiation with a wavelength of 300nm was 50kwh·m -2 , tested the performance stability under UV conditions, and the test results are shown in Table 1.
[0144] Table 1 Product performance test results of Examples 1-3 and Comparative Examples 1-11:
[0145]
[0146] It can be concluded from Examples 1-3 and Comparative Examples 1-11 that the product of Example 3 of the present invention has significant barrier properties and flame retardant properties under normal conditions, and the barrier properties and flame retardant properties of the product can be improved in a coordinated manner. In addition, the product has significant performance stability under ultraviolet conditions and high and low temperature conditions.
[0147] From Comparative Examples 1-11 and Example 3, it can be seen that the barrier properties and flame retardant properties of the products without adding any of the anti-adjustment agent and the filler based on halloysite modification have a significant deterioration trend, especially under ultraviolet conditions and high and low temperature conditions, the performance deterioration is more obvious. The anti-adjustment agent and the filler based on halloysite modification are used in combination to enhance the performance, and the performance effect of the product is the most significant;
[0148] No flake boron nitride regulating liquid was added to the resistance adjustment agent, no modified lanthanum chloride liquid was added in the preparation of flake boron nitride regulating liquid, the modified lanthanum chloride liquid was replaced by 3.5% lanthanum chloride solution by mass, and no resistance agent was added to the resistance adjustment agent. The performance of the products showed a trend of deterioration to varying degrees, especially when no resistance agent was added, the performance of the products deteriorated more significantly.
[0149] The performance of the products tended to deteriorate when the halloysite-modified filler was not treated with S101, the halloysite-modified filler was not treated with the filling modifier, hydroxyapatite liquid was not added to the filling modifier, stearic acid and wollastonite were not added to the filling modifier, and the dopamine hydrochloride solution was replaced by deionized water. The halloysite-modified filler obtained by using the hydroxyapatite liquid of the present invention in combination with the specific filling modifier of the present invention and treated with S101 had the most significant performance effect. The use of other raw materials instead was not as obvious as the effect of the present invention.
[0150] Based on the fact that the resistance agent has a significant impact on the performance of the product, further research is conducted on this.
[0151] Experimental Example 1:
[0152] The only difference from Example 3 is that no preheated nano bentonite is added in the preparation of the resistance agent.
[0153] Experimental Example 2:
[0154] The only difference from Example 3 is that nano zinc oxide is not added in the preparation of the resistance agent.
[0155] Experimental Example 3:
[0156] The only difference from Example 3 is that no chitosan solution is added during the preparation of the resistance agent.
[0157] Experimental Example 4:
[0158] The only difference from Example 3 is that no yttrium nitrate solution is added during the preparation of the resist.
[0159] Experimental Example 5:
[0160] The only difference from Example 3 is that sodium lignin sulfonate is not added in the preparation of the tolerance agent.
[0161] The flame retardant and barrier properties of the products of Experimental Examples 1-5 were tested by placing the products at -5°C for 24 hours, and then at 65°C for 24 hours. The test was repeated 5 times to test the high and low temperature stability of the products. The ultraviolet radiation with a wavelength of 300nm was 50kwh·m -2 , tested the performance stability under UV conditions, and the test results are shown in Table 2.
[0162] Table 2 Product performance test results of Experimental Examples 1-5:
[0163]
[0164] It can be seen from Experimental Examples 1-5 that the performance of the product deteriorated significantly when no preheated nano-bentonite was added in the preparation of the tolerance agent, followed by the performance of the product deteriorating when no nano-zinc oxide was added, the performance of the product deteriorated when no chitosan solution was added in the preparation of the tolerance agent, the performance of the product deteriorated when no yttrium nitrate solution was added in the preparation of the tolerance agent, and the performance of the product deteriorated when no sodium lignin sulfonate was added in the preparation of the tolerance agent.
[0165] Therefore, the performance effect of the product is most significant when the preheated nano bentonite of the present invention is combined with the nano zinc oxide of the present invention and the specific raw materials of the present invention. The performance effect of the product tends to deteriorate when other raw materials are used instead or the raw material components are missing in the preparation of the tolerance agent. Only the tolerance agent obtained by the specific method of the present invention has the most significant performance effect of the product. The effects of other methods are not as obvious as those of the present invention.
[0166] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0167] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An anti-ultraviolet TPU high and low temperature film, characterized in that: It includes the following raw materials in parts by weight: 75-85 parts of TPU resin, 8-12 parts of anti-adjustment agent, 6-9 parts of filler based on halloysite modification, 5-8 parts of silane coupling agent, 5-7 parts of flame retardant, 4-6 parts of heat stabilizer, 2-4 parts of lubricant, 2-5 parts of antioxidant; The preparation method of the resistant agent is as follows: S11: Add 2 to 3 parts of silane coupling agent KH550 and 1 to 3 parts of sodium alginate powder to 5 to 8 parts of lanthanum chloride solution by weight and mix well to obtain modified lanthanum chloride solution; S12: The flaky boron nitride is firstly mixed in a 4% potassium permanganate solution with a mass fraction of 3 to 5 times the total weight of the flaky boron nitride, and then washed with water and dried to obtain dry flaky boron nitride; Then, the dried flake boron nitride, sodium dodecylbenzene sulfonate solution and modified lanthanum chloride solution are mixed thoroughly in a weight ratio of (3-5):(4-7):2 to obtain a flake boron nitride regulating solution; S13: mixing the flake boron nitride adjusting liquid and the resistance agent in a weight ratio of 7:5, and ball milling the mixture at a speed of 1000-1200 r / min for 1 hour. After the ball milling is completed, washing and drying are performed to obtain the resistance agent; The preparation method of the resistance agent is: Preheating the nano-bentonite at 55-60° C. for 20 minutes to obtain preheated nano-bentonite; then adding 5-8 parts of the preheated nano-bentonite and 1-3 parts of nano-zinc oxide to 5-8 parts of 5% by weight yttrium nitrate solution, and then adding 2-4 parts of 4% by weight chitosan solution and 1-3 parts of sodium lignin sulfonate to mix and stir, and after stirring, filtering and drying to obtain a tolerizing agent; The preparation method of the filler based on halloysite modification is as follows: S101: soaking the halloysite in a sufficient amount of a sodium hydroxide solution having a mass fraction of 6%, and then washing, filtering and drying after the soaking is completed; Then stir evenly in a sufficient amount of 5% sodium citrate solution, wash with water, filter and dry; S102: mixing hydroxyapatite and 2-5% by mass sodium silicate solution in a weight ratio of 2:5 to obtain hydroxyapatite liquid; According to weight, 2 to 4 parts of stearic acid and 1 to 3 parts of wollastonite are added to 8 to 12 parts of dopamine hydrochloride with a mass fraction of 2 to 5%, and then 3 to 5 parts of hydroxyapatite liquid are added and mixed sufficiently to obtain a filling modifier; S103: The halloysite treated in S101 and the filling modifier obtained in S102 are mixed and ball-milled in a weight ratio of 5:
3. After the ball-milling is completed, the mixture is washed with water and dried to obtain a filling agent based on halloysite modification.
2. The anti-ultraviolet TPU high and low temperature film according to claim 1, characterized in that: The heat stabilizer is calcium stearate, the flame retardant is magnesium hydroxide; the lubricant is microcrystalline wax; the antioxidant is antioxidant 1010; and the silane coupling agent is silane coupling agent KH560.
3. The anti-ultraviolet TPU high and low temperature film according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-4%.
4. The anti-ultraviolet TPU high and low temperature film according to claim 1, characterized in that: The mixing speed of the blending and stirring process is 750-850 r / min, and the mixing time is 35-45 min.
5. The anti-ultraviolet TPU high and low temperature film according to claim 1, characterized in that: The soaking temperature of the soaking treatment in S101 is 48-52° C., and the soaking time is 1 hour. The rotation speed of the mixing ball milling treatment in S103 is 1000-1500 r / min, and the ball milling time is 35-45 minutes.
6. A method for preparing an anti-ultraviolet TPU high and low temperature film, used for preparing an anti-ultraviolet TPU high and low temperature film as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: The resistant filler, halloysite-modified filler, flame retardant and heat stabilizer are first stirred and mixed, and then sent into a film blowing machine together with TPU resin, silane coupling agent, lubricant and antioxidant for plasticization and extrusion to obtain a plasticized extrudate; the plasticized extrudate is blown and pulled, and then cooled, pulled and rolled to obtain a UV-resistant TPU high and low temperature film.
7. The method for preparing a UV-resistant TPU high and low temperature film according to claim 6, characterized in that: The feeding temperature in the film blowing machine is 135-140°C, the temperature of the plasticizing section is 170-175°C, and the die head temperature is 150°C; the blowing ratio of the inflation traction is 2.7-2.9, and the traction ratio is 4-6.
Citation Information
Patent Citations
Environment-friendly water-based high and low temperature film and preparation method thereof
CN118684928A